USING GRAPHIC CALCULATOR IN TRIGONOMETRIC LEARNING: A DIDACTICAL DESIGN FOR TEACHER - Churun Lu’lu’il Maknun; Rizky Rosjanuardi; Al Jupri (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This study explored the activitiesusing a graphing calculator of 10th-grade high school students on the trigonometry topic. A total of 65 students were divided into two classes, the first class consisted of 32 students, and the second class consisted of 33 students. The main objective of this study is to present classroom activities enriched with graphing calculators and observe responses about teaching with this approach. This study is research on developing learning designs within the Didactical Design Research (DDR) framework presented in an exploratory narrative. Data were collected by using two trigonometry worksheets and lesson observations. The worksheets were constructed based on the following focus areas: behaviour of graphs, constructing related-angle formula, and overall performance of the learner. The result of this research is a learning design that has been tested on 65 high school students. The research results on how to analyze the results of the implementation of structured learning designs provide information that educators can use, including the use of graphing calculators to help and make it easier for students to identify graphs more quickly and make students accustomed to using trigonometric function symbols. Another finding from structured instructional designs is that working in groups allows students to share experiences more effectively.